2021
DOI: 10.3390/su131911003
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions and Problematic Internet Use among University Students: The Mediator Role of Self-Esteem

Abstract: Information and communication technologies are transforming our daily lives in a wide variety of ways, such as the way we work, study, and interact with others. There are clear benefits to be gained from appropriate use, but a problem arises when addictive and problematic use of the Internet is experienced. In this sense, several predictive factors can be related to inappropriate or problematic Internet use. For this reason, the present study aimed to analyze whether inhibition, flexibility, emotional control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…There is evidence on the relationship between goal setting and the promotion of autonomy support in physical education lessons, producing positive effects on leisure-time physical activity-related cognition [ 10 ]. According to Pichardo et al [ 11 ], emotional control is one the variables with the most direct effects on PTU . Some studies found that low levels of emotional regulation or impulsive behaviors were related to PTU [ 12 ], or to intensive mobile phone use [ 13 , 14 ].…”
Section: Executive Functions: Goal Setting and Inhibitory Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence on the relationship between goal setting and the promotion of autonomy support in physical education lessons, producing positive effects on leisure-time physical activity-related cognition [ 10 ]. According to Pichardo et al [ 11 ], emotional control is one the variables with the most direct effects on PTU . Some studies found that low levels of emotional regulation or impulsive behaviors were related to PTU [ 12 ], or to intensive mobile phone use [ 13 , 14 ].…”
Section: Executive Functions: Goal Setting and Inhibitory Controlmentioning
confidence: 99%
“…(c) Inhibitory control would be associated with a lower level of PTU. Deficits in emotional control have been linked to PTU [ 11 , 12 ] as well as to intensive mobile phone use [ 13 , 14 ]. Moreover, it is known that self-regulation has been found to be a predictor of adaptive development across many domains [ 18 ].…”
Section: Objectives and Hypothesesmentioning
confidence: 99%
“…According to Pichardo et al (2021) exibility and emotional control are the variables with the most direct effects on PTU. A recent study based on 3,831 school-going adolescents aged 13 to 18 years showed that goal setting as well as inhibitory control inversely predicted PTU (Albertos & Ibabe, 2021).…”
Section: Executive Functions: Goal Setting and Inhibitory Controlmentioning
confidence: 99%
“…In addition, current research has not found any study directly exploring the mediating role of self-esteem between physical activity and Internet addiction. Instead, most studies investigate the role of self-esteem in Internet addiction from other psychological perspectives, such as the family atmosphere [ 22 ], the need to belong [ 23 ], and the executive function [ 24 ]. However, all of the above studies may imply, either positively or negatively, that physical activity can increase individual’s level of self-esteem, and that the level of self-esteem is negatively related to Internet addiction.…”
Section: Introductionmentioning
confidence: 99%